Economic Impact of Covid-19 Pandemic on Sports Tourism in Kwara State, Nigeria - Abdulraheem Mulikat; Falaye Elijah Kayode (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
Sport tourism serve as economic catalyst of any Nation, therefore, this study investigated Economic impact of covid-19 pandemic on sports tourism in Kwara State. The objectives of this study were to: (i) evaluate the relationship between sports income generated on sports centers and closure of hotels and sports tourism. Descriptive research design of survey type was used for the study. The population of the study comprised of all Hoteliers, staff of sports council and sports marketers. Stratified and purposive sampling technique was used to select 100 respondents. Researchers designed questionnaire was used for the study. The instrument was validated by lecturers in the Department of Human Kinetics Education University of Ilorin and lecturers in the Department of Human Kinetic & Health Education, Kwara State University. A correlation coefficient of 0.68 was obtained. The instrument was administered by the researchers. The data collected were analysed using inferential statistic of Pearson Product Moment Correlation (PPMC). The result of the findings revealed that income generated on sports centers, closure of hotel have economic impact and sport tourism during covid-19 pandemic in Kwara State. Based on the findings of this study, it was recommended that people should be encouraged to embark on digitalization of sports in term of sales of sports products and viewing of sports events on social media so as to enhance effective participation in sports tourism.